PEMANFAATAN PADLET DAN PENGENALAN ZOTERO DALAM SEMINAR PENULISAN KARYA TULIS ILMIAH BAGI MAHASISWA STIT MASKUMAMBANG GRESIK - Muhamad Afif Effindi; Medika Risnasari; Nanda Afdholul Basyar (Politeknik Negeri Sriwijaya, 2023)
Sekolah Tinggi Ilmu Tarbiyah (STIT) Maskumambang (Maskumambang College of Tarbiyah), Gresik Regency, fully understands the importance of improving students' writing skills. This was conveyed through holding seminars on writing scientific papers for students. This article presents the results of holding a scientific paper writing seminar for students, with a focus on using the Padlet and introduction to Zotero. The results of the questionnaire on the participants showed that in terms of student experience in using Zotero, only 5 percent of students had ever used it. The remaining 92 percent have never used Zotero. Meanwhile, from the suggestions column for the implementation of the training, one of the participating students was stated to be good. However, the training held did not provide enough writing practice sessions for participating students. This is understandable considering the format of the event is a seminar.